Focusing Highly Squinted FMCW-SAR Data Using the Modified Wavenumber-Domain Algorithm - Tinghao Zhang; Yachao Li; Mingze Yuan; Liang Guo; Jiao Guo; Hao Lin; Mengdao Xing (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The three-dimensional (3-D) acceleration, azimuth dependence, and real-time processing are the main issues to be solved in highly squinted frequency-modulation continuous-wave (FMCW) synthetic aperture radar (SAR) with a curved trajectory. To overcome these issues, a modified wavenumber-domain algorithm is developed in this article. The proposed modified wavenumber-domain algorithm mainly includes the following six aspects. First, a modified range model considering 3-D acceleration for a curved trajectory is established. Then, the spectrum compression and rotation operations are performed to guarantee further processing. Afterward, residual phase terms introduced by acceleration are bulk compensated for. Moreover, the azimuth dependence is eliminated by the azimuth resampling to achieve uniform focusing. Subsequently, the range–azimuth coupling is removed by the modified Stolt interpolation. Finally, to avoid image aliasing, the azimuth wavenumber domain is selected to focus the final image. The experimental results of both numerical and raw-measured FMCW-SAR data demonstrate the superiority of the proposed method.